2015
DOI: 10.1111/jgh.13013
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term course of Crohn's disease in Japan: Incidence of complications, cumulative rate of initial surgery, and risk factors at diagnosis for initial surgery

Abstract: Stenosis or fistula appeared in about half of the patients after 5 years from diagnosis. When upper gastrointestinal disease or complicated small intestinal lesions are seen at the time of diagnosis, the cumulative rate of initial surgery is significantly higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…Intestinal complications of Crohn's disease include obstruction and perforation of the small intestine or colon, abscesses (collections of pus), fistulae, and intestinal bleeding. 13,14 When patients with IBD develop abdominal pain with hyperamylasemia in perforated viscus, they may be misdiagnosed with acute pancreatitis. 15,16 This is another cause of the increased risk of acute pancreatitis in patients hospitalized with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal complications of Crohn's disease include obstruction and perforation of the small intestine or colon, abscesses (collections of pus), fistulae, and intestinal bleeding. 13,14 When patients with IBD develop abdominal pain with hyperamylasemia in perforated viscus, they may be misdiagnosed with acute pancreatitis. 15,16 This is another cause of the increased risk of acute pancreatitis in patients hospitalized with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cumulative rate of initial surgery also increased with time with the majority of patients having undergone surgery at 10 years after diagnosis. When upper gastrointestinal disease or complicated small intestinal lesions were seen at the time of diagnosis, the cumulative rate of initial surgery was significantly higher [13] . Interestingly, a complete and long-standing fistula closure was not consistently observed with treatment with any of the routinely used CD medications [14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic outcome is often insufficient to achieve fistula closure, and surgical treatment is frequently required [12] . In a recently published single-center retrospective cohort study in Japan, it was shown that stenoses and fistulae increased with time, with stenoses or fistulae appearing in about half of the patients after 5 years [13] . Furthermore, the cumulative rate of initial surgery also increased with time with the majority of patients having undergone surgery at 10 years after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the patients with a definitive diagnosis of CD who had a history of visiting our hospital between May 1967 and December 2015, patients with a history of treatment for at least 6 months since diagnosis were selected, and a database based on their medical records was subsequently created [3]. Patients who were followed up for less than 6 months after diagnosis were excluded.…”
Section: Study Design and Populationsmentioning
confidence: 99%
“…It often develops at an early age and can affect the entire gastrointestinal tract from the oral cavity to the anus. It is also known to frequently require intestinal resection due to the development of intestinal complications such as stenosis and fistula through repeated relapses or recurrences [1][2][3][4]. Although there are some reports of the long-term course of patients with this disease, there are very few reports related to their survival and cause of death; moreover, most previous reports are derived from population-based cohort studies, and there are very few, long-term, hospital-based, cohort studies with a long duration of follow-up and a large sample size [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%